2020
DOI: 10.2147/ijgm.s253246
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Serum Level of FGF23 and 1,25(OH)<sub>2</sub>D<sub>3</sub> in Primary Hyperparathyroidism Patients Before and After Parathyroidectomy</p>

Abstract: Purpose: Parathyroid hormone (PTH) and fibroblast growth factor 23 (FGF23) play critical roles in phosphate homeostasis. To the best of our knowledge, there are limited data on the impact of FGF23 and PTH on serum calcium, 1,25(OH) 2 D 3 , and phosphate in patients with primary hyperparathyroidism (PHPT). We examined these parameters and their correlations in PHPT patients before and after parathyroidectomy (PTX). Patients and Methods: In this prospective cohort study, 29 PHPT patients who met the inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Bilha et al also mentioned that some patients followed up prospectively for up to 12 months after surgery showed constant cFGF23 levels, despite PTH and calcium normalization and vitamin D replenishment. Hassani et al ( 33 ) showed positive correlation of FGF23 with 1,25(OH) 2 D preoperatively and postoperatively (24 h and 1 week after the operation), and they did not prove significant correlations between FGF23, calcium, phosphate and PTH.…”
Section: Discussionmentioning
confidence: 92%
“…Bilha et al also mentioned that some patients followed up prospectively for up to 12 months after surgery showed constant cFGF23 levels, despite PTH and calcium normalization and vitamin D replenishment. Hassani et al ( 33 ) showed positive correlation of FGF23 with 1,25(OH) 2 D preoperatively and postoperatively (24 h and 1 week after the operation), and they did not prove significant correlations between FGF23, calcium, phosphate and PTH.…”
Section: Discussionmentioning
confidence: 92%
“…Studies on the clinical role of FGF-23 in PHPT are scarce, although this hormone might have a potential role in the severity of clinical manifestations or symptoms in these patients. Twenty-nine PHPT patients were evaluated prospectively before and after parathyroidectomy [ 19 ]. The authors found that 1.25(OH) 2 vitamin D levels correlated with FGF-23 levels both preoperatively and postoperatively, although they could not find any other significant relationship with calcium, phosphate, and PTH.…”
Section: Phosphate In Primary Hyperparathyroidismmentioning
confidence: 99%
“…The fibroblast growth factor 23 (FGF-23) is a peptide secreted by the osteocytes and osteoblasts, at present considered to be a regulator of the calcium–phosphate balance and an important element of the FGF-23-bone–kidney axis. FGF-23 enhances urinary phosphate excretion and inhibits the production of the active form of vitamin D. The importance of FGF-23 in PHPT patients has been recently described [ 6 ].…”
Section: Introductionmentioning
confidence: 99%